2021
DOI: 10.3389/fendo.2021.560055
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipid Modulation of Intestinal Serotonin in Ballan Wrasse (Labrus bergylta)—In Vitro Analyses

Abstract: Serotonin (5-HT) is pivotal in the complex regulation of gut motility and consequent digestion of nutrients via multiple receptors. We investigated the serotonergic system in an agastric fish species, the ballan wrasse (Labrus bergylta) as it represents a unique model for intestinal function. Here we present evidence of the presence of enterochromaffin cells (EC cells) in the gut of ballan wrasse comprising transcriptomic data on EC markers like adra2a, trpa1, adgrg4, lmxa1, spack1, serpina10, as well as the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…A transcriptomic study was performed on agastric fish members, specifically the ballan wrasse chosen for its distinctive characteristics related to intestinal function which showed the presence of various biomarker genes like ADGRG4 in the enterochromaffin cells. [30] The past decade has seen significant progress in understanding the active signaling pathways of GPCR research. Despite this, the physiological roles of these receptors, especially in cancer development and metastasis, remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A transcriptomic study was performed on agastric fish members, specifically the ballan wrasse chosen for its distinctive characteristics related to intestinal function which showed the presence of various biomarker genes like ADGRG4 in the enterochromaffin cells. [30] The past decade has seen significant progress in understanding the active signaling pathways of GPCR research. Despite this, the physiological roles of these receptors, especially in cancer development and metastasis, remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptomic study was performed on agastric fish members, specifically the ballan wrasse chosen for its distinctive characteristics related to intestinal function which showed the presence of various biomarker genes like ADGRG4 in the enterochromaffin cells. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns were also observed for the transcripts involved in the TAG pathway (mogat, agpat4). A recent study by Etayo et al (2021) in ballan wrasse (Labrus bergylta) fed lipid rich meal, reported the initial increase in gene expression involved in serotonin synthesis and then declined over time post-prandially.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, we observed very low expression of apob, and although other apolipoproteins (apoa1, apoa4, apoc, apoe, and apod) were expressed, no DEGs for any of these apolipoproteins in all treatment groups, including control. This might be related to the time points at which the cells were sampled after FAs exposure as described in Etayo et al (2021).…”
Section: Discussionmentioning
confidence: 99%